MANAGEMENT STRES, COPING STRES PADA REMAJA DAN DAMPAK PADA PEMBANGUNAN EKONOMI DAERAH KOTA TERNATE - Nurlaila Nurlaila (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2019)
Adolescence is a period where the transition from childhood to adulthood, not only that they also do not form physical maturity (hacking) but will also lead to social-psychological maturity, among others, towards maturity and independence (Ruwaida, 2006 ) This study uses a qualitative method to describe stress management coping in adolescents as a result of parental divorce through a phenomenological approach which focuses on finding facts of human behavior based on the informant's perspective. Methods of collecting data through in-depth interviews and completed with field notes. The research subjects were teenagers whose parents divorced with the age limit (15-22 years) the number of subjects in this case study was 14 (fourteen) people in Ternate City. The behavior and culture of life of informants due to not being able to manage stress and accept family conditions, there is no visible achievement of the informants for regional economic development. very influential in regional development considering that the younger generation is the successor of the nation and state development. The results of this research indicate the condition of adolescents who experience problems such as this affect the development of development when viewed from the achievements that should be owned by the younger generation.